RESONANSI OBJEK WISATA DENGAN NILAI ERGO-IKONIK UNTUK PENGEMBANGUN BERKELANJUTAN - Chandra Murti Dewi Widowati Hermajiwandi; Hubertina Karolina Ngarbingan; Indar Fauziah Ulfah; Yudhi Prasetiyo; Raden Abdurrohman Thohir Wijaya; Andriyansah Andriyansah (Universitas Mahendradatta Denpasar, 2024)
This research aims to complete or fill the research gap conducted by previous researchers related to sustainable tourism development. This research uses a quantitative approach with a survey technique of 50 responses conducted during the April 2024 joint leave at the Belitung island tourist attraction. This research found that tiktok, natural, no additional costs, halal culinary are important points for tourists when deciding to travel. aligning tourist attraction development with these values, destinations can increase visitor satisfaction, preserve cultural and natural heritage, encourage local community involvement, and promote responsible and sustainable tourism practices. To achieve this resonance, tourist destination development should engage local stakeholders, adopt a place-based approach, apply ergonomic and eco-friendly design principles, authentically interpret cultural and natural heritage, and monitor and manage tourism impacts. The resonance of tourist attractions with ergo-iconic values can create meaningful tourism experiences and contribute to sustainable tourism development.